2011
DOI: 10.1002/joc.2334
|View full text |Cite
|
Sign up to set email alerts
|

Skill of monthly rainfall forecasts over India using multi‐model ensemble schemes

Abstract: Rainfall in the month of July in India is decided by large-scale monsoon pattern in seasonal to interannual timescales as well as intraseasonal oscillations. India receives maximum rainfall during July and August. Global dynamic models (either atmosphere only or coupled models) have varying skills in predicting the monthly rainfall over India during July. Multi-model ensemble (MME) methods have been utilized to evaluate the skills of five global model predictions for . The objective has been to develop a predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 35 publications
0
40
0
Order By: Relevance
“…The last two models, referred to as ECHcasst and ECHcfssst, are two twotier versions of ECHAM4.5 forced with constructed analog SST and CFS forecast SST (Li and Goddard, 2005), respectively. All these models are also discussed in detail in Kar et al (2011). The number of ensemble members and spatial resolution of these models are given in Table 1.…”
Section: Model and Observed Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The last two models, referred to as ECHcasst and ECHcfssst, are two twotier versions of ECHAM4.5 forced with constructed analog SST and CFS forecast SST (Li and Goddard, 2005), respectively. All these models are also discussed in detail in Kar et al (2011). The number of ensemble members and spatial resolution of these models are given in Table 1.…”
Section: Model and Observed Datamentioning
confidence: 99%
“…Kang et al, 2004;Krishna Kumar et al, 2005;Sahai et al, 2008;Pattanaik and Kumar, 2010;Acharya et al, 2011;Janakiraman et al, 2011;Kar et al, 2011). Preethi et al (2010) have analysed the skill of some of the coupled models for the hind-cast run from 1959 to 1979 and found the skill of the models to be positive.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the simulation of South Asian summer monsoon precipitation by RegCM is sensitive to the physics parameterization used. Kar et al [33] and Acharya et al [34] also found that RCM has some systematic biases while simulating the summer monsoon precipitation over this region. As described in section 2.1.3, RegCM4.3 simulated excessive precipitation with the MIT convective scheme.…”
Section: Precipitation Climatology For Summer Season (Jja)mentioning
confidence: 90%
“…Advances in Meteorology schemes were tested on the Indian region for rainfall forecast [19][20][21]. On examination of 5-multimodel schemes they realized that the accuracy of the rainfall forecasts can be increased over Indian region.…”
Section: Introductionmentioning
confidence: 99%